Trust under bounded rationality: Competence, value systems, unselfishness and the development of virtue - Natàlia Cugueró; Josep M. Rosanas (Intangible Capital, 2019)
Purpose: This paper analyses the foundations of trust in a context of bounded rationality to arrive to the conclusion that for trust to be necessary is because individuals are bounded rational.